AMAP Arctic Ocean Acidification Assessment: Key Findings. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2013)
Key findings summarized from AMAPs Arctic Ocean Acidification Assessment.